2021
DOI: 10.1002/cnma.202100226
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stability of Metal‐organic Frameworks for Applications in Drug Delivery

Abstract: Structural variety, tunable porosity and opportunities for functionalization make metal‐organic frameworks (MOFs) promising materials for applications in medicine as drug delivery systems. In this minireview, an overview of chemical stability of MOF nanocarriers at simulated body conditions is presented. Parameters such as a choice of buffer, pH value, nanoparticle size or surface modification are discussed, as well as analytical methods and approaches suitable to determine the material stability. Last but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 62 publications
0
42
0
Order By: Relevance
“…They reported that PCN-224 with a particle size of 90 nm loaded with a photosensitizer were better performing in photodynamic therapy than PCN-224 with a particle size of 190 nm. Moreover, since MOFs are considered to be intrinsically biodegradable, the particle size influences also the overall carrier stability ( Bunzen, 2021 ). For instance, Falcaro et al reported on the chemical stability of ZIF-8 with regard to the particle size ( Velásquez-Hernández et al, 2019 ).…”
Section: The Importance Of Crystal Size and Morphology In Drug Deliverymentioning
confidence: 99%
“…They reported that PCN-224 with a particle size of 90 nm loaded with a photosensitizer were better performing in photodynamic therapy than PCN-224 with a particle size of 190 nm. Moreover, since MOFs are considered to be intrinsically biodegradable, the particle size influences also the overall carrier stability ( Bunzen, 2021 ). For instance, Falcaro et al reported on the chemical stability of ZIF-8 with regard to the particle size ( Velásquez-Hernández et al, 2019 ).…”
Section: The Importance Of Crystal Size and Morphology In Drug Deliverymentioning
confidence: 99%
“…128−130 Wang et al reported on a pH-responsive fluorinated ZIF for in vitro and in vivo 19 F MRI. 128 ZIF-8 comprises Zn(II) ions and 2-methylimidazolate ligands and is known to be pHresponsive (stable at neutral and slightly basic conditions, but rather unstable in acidic conditions 131,132 ). In this work, some of the ligands were exchanged to 4-(trifluoromethyl)imidazole to provide the fluorine moieties for the detection by 19 F MRI.…”
Section: Mofs In Heteronuclear Mrimentioning
confidence: 99%
“…64,65 As discussed by McKinlay et al, one of the biggest potential drawbacks for MOFs is their chemical stability, which happens to depend on several factors such as the operating environment, temperature, pH conditions, and particle size. 66,67 The enhanced chemical instability of MOFs could actually be a desirable characteristic, as it would prevent an endogeneous accumulation of potentially toxic ions and MOF precursors in the living system. 64 Control over the physical and chemical properties of MOFs via biofunctionalization could ensure a stability of up to several days, or even weeks, which would be enough to ensure completion of its intended function, such as drug delivery, bio-sensing or bio-imaging.…”
Section: Applications Of Biofunctionalized Mofsmentioning
confidence: 99%